Gastroenteritis Caused by Norovirus GGII.4, the Netherlands, 1994–2005 - Siebenga, J. Joukje (Centers for Disease Control and Prevention, 2007)
From 1994 through 2005, gastroenteritis outbreaks caused by norovirus generally increased in the Netherlands, with 3 epidemic seasons associated with new GGII.4 strains. Increased percentages of GGII.4 strains during these epidemics, followed by a sharp decrease in their absolute and relative numbers, suggest development of immunity.